2011
DOI: 10.1096/fj.10-179234
|View full text |Cite
|
Sign up to set email alerts
|

Strain‐specific vulnerability to alcohol exposure in utero via hippocampal parent‐of‐origin expression of deiodinase‐III

Abstract: Prenatal exposure to alcohol is thought to be the most prevalent nongenetic cause of a wide range of neurodevelopmental deficits. Insufficient thyroid hormone levels are one mechanism that hampers development of the alcohol-exposed brain, and we hypothesized that altered dosage of the imprinted thyroid hormone-inactivating gene deiodinase-III (Dio3) is responsible. To follow parent-of-origin allelic expression of Dio3 in the fetal and adult offspring of alcohol-consuming and control dams, we reciprocally cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
79
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(85 citation statements)
references
References 83 publications
5
79
1
Order By: Relevance
“…In fact, this was confirmed when different in vitro systems were used to assess the impact of increased thyroid hormone signaling in the ␤-cells. Exposing pancreatic explants (Figure 4, A and B), isolated pancreatic islets (Figure 4, C-G), or D3-expressing It is interesting that Dio3 is paternally imprinted in the mouse heart (10) and, in turn, maternally imprinted in the pancreatic ␤-cells, which is in agreement with reports that Dio3 expression is biallelic or maternally expressed in certain areas of the brain (23,24). In fact, the mechanisms involved in the allelic-specific Dio3 expression are complex.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In fact, this was confirmed when different in vitro systems were used to assess the impact of increased thyroid hormone signaling in the ␤-cells. Exposing pancreatic explants (Figure 4, A and B), isolated pancreatic islets (Figure 4, C-G), or D3-expressing It is interesting that Dio3 is paternally imprinted in the mouse heart (10) and, in turn, maternally imprinted in the pancreatic ␤-cells, which is in agreement with reports that Dio3 expression is biallelic or maternally expressed in certain areas of the brain (23,24). In fact, the mechanisms involved in the allelic-specific Dio3 expression are complex.…”
Section: Discussionsupporting
confidence: 89%
“…The paternal allele contribution of Dio3 is 84% in embryonic mouse tissue, whereas in placenta it varies between 50% and 67% (22). At the same time, Dio3 expression has been reported to be biallelic or even maternally expressed in certain areas of the brain (23,24). These different imprinting patterns have led to the study of heterozygous (Htz)-D3KO animals, with the advantage that these animals exhibit normal thyroid economy (10).…”
mentioning
confidence: 99%
“…Additionally, impaired hippocampus-dependent spatial and social learning/memory is shown both in animal models of FASD (Wilcoxon et al, 2005, Sittig et al, 2011b, Weeber et al, 2001, Tunc-Ozcan et al, 2013) and FASD patients (Hamilton et al, 2003). It appears likely that many of the cognitive and behavioral deficits of FASD may involve the compromised neurodevelopment of the hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical (21, 30, 52) and preclinical (4, 23, 33, 35, 46) studies have reported that fetal programming by alcohol results in HPA dysregulation, including both hyperresponsiveness to stressors and deficits in recovery to basal levels. While mechanisms mediating these adverse effects of alcohol are starting to be elucidated (23,55,59,60,71), the molecular pathology underlying fetal alcohol effects on the HPA axis is not fully understood.Accumulating evidence suggests that the interplay between environmental factors and epigenetic processes, such as DNA methylation and chromatin modifications, could play a role in mediating the adverse effects of PAE, including its effects on HPA regulation (20,22,38). Alcohol-induced alterations in one-carbon metabolism provide one potential link between alcohol exposure and epigenetic processes.…”
mentioning
confidence: 99%
“…Clinical (21,30,52) and preclinical (4,23,33,35,46) studies have reported that fetal programming by alcohol results in HPA dysregulation, including both hyperresponsiveness to stressors and deficits in recovery to basal levels. While mechanisms mediating these adverse effects of alcohol are starting to be elucidated (23,55,59,60,71), the molecular pathology underlying fetal alcohol effects on the HPA axis is not fully understood.…”
mentioning
confidence: 99%